Evaluation of the effectiveness of vitamin E in nonalcoholic fatty liver disease among type 2 diabetes patients without advanced fibrosis - Miranda Manrique, Gonzalo (2023)
Objective: To determine the effectiveness of vitamin E in nonalcoholic fatty liver disease (NAFLD) among type 2 diabetes patients without advanced fibrosis.Materials and methods: A quasi-experimental analytical study consisting of two groups: an experimental one, which received vitamin E 400 IU in addition to the standard treatment, and a control group, which received only the standard treatment. The study included 71 patients in each group. Both groups underwent liver fibrosis scoring, liver ultrasound and glutamate pyruvate transaminase measurement at study baseline and after six months. Moreover, the Wilcoxon test was used to compare the concentrations of fibrosis score and glutamate pyruvate transaminase values within the same group, and the Mann-Whitney U test was used to evaluate the differences between the experimental and control groups. The Wilcoxon test was also used to compare ultrasound severity. Then, a logistic regression analysis was performed. The information was entered into a data collection sheet using Microsoft Excel; afterwards, a database was coded and created using IBM SPSS Statistics statistical software 23.0. Results: Among the results, it was found that vitamin E was significantly effective in reducing liver fibrosis, transaminase and ultrasound severity scores (Z = -4.727 and p < 0.05). According to the logistic regression analysis, glutamate pyruvate transaminase levels and fibrosis score are not substantially explained by the confounding variables included in the model at 95 % confidence. Conclusions: Vitamin E at a dose of 400 IU given orally for six months is an effective intervention to control the progressionof liver disease, which can be quantified by fibrosis score, transaminase reduction and ultrasound assessment after a 6-month follow-up.